Compressive Strength of Concrete with Malang Sand as Fine Aggregate Substitute - Santoso, Muhammad Iqbal Paramatatya Satyawan; Bali, Ika (President University, 2024)
Malang sand has small and rough grains with a sharp surface, it can easily absorb water and adhere to cement. It is very suitable for use as fine aggregate in concrete to improve the quality and durability of concrete. As sand from a volcano, Malang sand has similar characteristics to sand from cold lava resulting from volcanic eruptions. In another study, concrete with sand from cold lava of Sinabung volcano was reported to have the highest compressive strength in a mixture variation of 60-70% of Sinabung sand at the age of 14 days. This study focuses on investigating the compressive strength of concrete with the addition of Malang sand as partly replacement of 50-70% of the fine aggregate material. The concrete design method uses practical guidelines for designing concrete mixes according to Indonesian standard (SNI), and for testing the compressive strength of concrete using ASTM C-39. The percentage of sand used in this study is 50%, 60%, and 70% as a substitute for fine aggregate with a concrete age of 28 days. Based on the study results, the maximum average compressive strength is achieved for the concrete with Malang sand of 70% (MSC 70%) with a compressive strength of 31.89 MPa or an increase 4.32% compared to normal concrete. In this study indicated that the trend of compressive strength is increase with the increase of Malang sand content in the concrete.